Strategi Pemberitaan Media Harian Haluan Dalam Menghadapi Persaingan Media Online - mariyam, siti; Tresnawaty, Betty; Hardi, Nora Meilinda (Annaba: Jurnal Ilmu Jurnalistik, 2024)
This study aims to find out how the Haluan Daily media strategy faces the fierce competition of online media that continues to emerge by using Everett M. Rogers' Innovation Diffusion theory which explains how new ideas, products, or practices spread in society through various stages. Where these stages are Relative Advantage, Complexity, Trialability, Observability, and Compatibility. This study uses a qualitative approach with a descriptive method. The results of the study show that the media reporting strategy of Haluan Daily is in accordance with the theory of Innovation Diffusion. Starting from the Relative Advantage stage by highlighting the benefits or added value of the news conveyed. Complexity is seen in the web system it runs. Trialability is seen in interactive web views. Observability, by optimizing visibility on Google's search engine. Compatibility where the Haluan Daily has a format adjustment in the form of rules or Journalistic principles that he holds.